A Dictionary of Sociology - Scott, John; Marshail, Gordon (New York Oxford University Press, 2005)
This wide-ranging and authoritative book is the most informative sociology dictionary of its kind available. Compiled by a team of sociology experts, it is packed with over 2,500 entries. Each entry is elaborated with a clear description and in-depth analysis, and real-life examples are given wherever possible. Coverage is extensive, and includes terms from the related fields of psychology, economics, anthropology, philosophy, and political science.
This new edition, edited by Professor John Scott, has been revised to bring the dictionary completely up to date while retaining the concise, clear editorial quality of the previous editions. New features include boxed-in entries covering key aspects of sociology and weblinks to quality sociological websites. Seventy new entries cover everything from adaptation to orientalism. This edition also contains a range of new biographies covering key figures, such as Gilles Deleuze and Erich Fromm. It is both an invaluable introduction to sociology for beginners and a useful aid for more advanced students and teachers
Keywords: Sociology - Dictionaries